Performance Study Of Energy Recovery System With Two Different Sizes Of Heat Exchanger Under Hot-Humid Environment - Abul Rahman, Siti Masitah (2018)
This thesis reports the theoretical and experimental analysis of energy recovery system with two different sizes of heat exchangers under hot-humid environment. The heat exchangers were made of membrane based material with cross-flow arrangement with an ability to transfer both sensible and latent heat from hot-humid intake airstream. The two different sizes heat exchangers i.e. smaller size and bigger size were compared with theoretical and experimental analysis. In the theoretical and experimental analysis, Number of Transfer Unit-effectiveness method and ASHRAE standard method were used. The performance of the heat exchangers was analysed based on the operating parameters namely air velocity, intake temperature, relative humidity and recovered energy. The results showed that as the air velocity increased, the effectiveness of energy recovery system decreased.